2001
DOI: 10.1083/jcb.200108159
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic release of CD44 intracellular domain and its role in the CD44 signaling pathway

Abstract: CD44 is a widely distributed cell surface adhesion molecule and is implicated in diverse biological processes. However, the nature of intracellular signaling triggered by CD44 remains to be elucidated. Here, we show that CD44 undergoes sequential proteolytic cleavage in the ectodomain and intracellular domain, resulting in the release of a CD44 intracellular domain (ICD) fragment. Consequently, CD44ICD acts as a signal transduction molecule, where it translocates to the nucleus and activates transcription medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
343
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(360 citation statements)
references
References 27 publications
11
343
0
2
Order By: Relevance
“…The transduction of HA/CD44 signaling can occur through various mechanisms including the following: i) HA binding to CD44 can initiate the extracellular clustering of CD44, resulting in the activation of downstream kinases, 14 ii) CD44 can serve as a co-receptor physically associated with other cell signaling receptors, [15][16][17][18] iii) CD44 can serve as a docking protein for pericellular or cytoplasmic proteins, 19,20 and iv) the transmembrane domain of CD44 can be cleaved, allowing the translocation of the cytoplasmic domain to the nucleus, where it functions as a transcription factor regulating the expression of target genes such as CD44 itself. 21,22 CD44 and its variants can induce chemoresistance and invasion of human BC cell lines via different mechanisms. [23][24][25][26][27] Despite knowing the role that CD44 -HA plays in promoting BC invasion and metastasis, the underlying downstream signaling mechanism is nascent.…”
mentioning
confidence: 99%
“…The transduction of HA/CD44 signaling can occur through various mechanisms including the following: i) HA binding to CD44 can initiate the extracellular clustering of CD44, resulting in the activation of downstream kinases, 14 ii) CD44 can serve as a co-receptor physically associated with other cell signaling receptors, [15][16][17][18] iii) CD44 can serve as a docking protein for pericellular or cytoplasmic proteins, 19,20 and iv) the transmembrane domain of CD44 can be cleaved, allowing the translocation of the cytoplasmic domain to the nucleus, where it functions as a transcription factor regulating the expression of target genes such as CD44 itself. 21,22 CD44 and its variants can induce chemoresistance and invasion of human BC cell lines via different mechanisms. [23][24][25][26][27] Despite knowing the role that CD44 -HA plays in promoting BC invasion and metastasis, the underlying downstream signaling mechanism is nascent.…”
mentioning
confidence: 99%
“…Previous data showed that CD44-ICD stimulates p300-mediated transactivation (33). Thus, we cotransfected CD44-ICD with p300 or a p300-dominant negative construct (LYRR; ref.…”
Section: Cd44-icd Stimulates Cre-mediated Transcriptionmentioning
confidence: 99%
“…(ii)Cleavage and subsequently translocation of the cytoplasmic tail of CD44 into the nucleus followed by transcription of several target genes inclusive the CD44 gene itself [57]. and enhanced cell motility [59].…”
Section: Intracellular Signaling Cascadesmentioning
confidence: 99%